Specific aspects of the activities of local self-government or public organizations in the foreign countries, governing the protection of the protection of the rights of persons with disabilities - Kohanchuk, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article examines some aspects of the activities of local self-government bodies and the public in foreign countries aimed at ensuring the rights of persons with disabilities. It is proposed to implement the experience of individual countries in the national legislation in order to improve the activities of public administration actors